Soil Temperature Variability in Complex Terrain Measured Using Fiber‐Optic Distributed Temperature Sensing. Issue 6 (17th June 2016) - Seyfried, Mark; Link, Timothy; Marks, Danny; Murdock, Mark
Abstract : Core Ideas: Soil temperature variability within land surface units is low, with a SD of <1.5°C. Land surface effects are greater than a 911‐m elevation change. Fiber‐optic DTS provides a unique look at soil temperature variability. Soil temperature ( T s ) exerts critical controls on hydrologic and biogeochemical processes, but the magnitude and nature of T s variability in a landscape setting are rarely documented. Fiber‐optic distributed temperature sensing (DTS) systems potentially measure T s at high density across a large extent. A fiber‐optic cable 771 m long was installed at a depth of 10 cm in contrasting landscape units (LUs) defined by vegetative cover at Upper Sheep Creek in the Reynolds Creek Experimental Watershed (RCEW) and Critical Zone Observatory in Idaho. The purpose was to evaluate the applicability of DTS in remote settings and to characterize T s variability in complex terrain. Measurement accuracy was similar to other field instruments (±0.4°C), and T s changes of approximately 0.05°C at a monitoring spatial scale of 1 m were resolved with occasional calibration and an ambient temperature range of 50°C. Differences in solar inputs among LUs were strongly modified by surface conditions. During spatially continuous snow cover, T s was practically homogeneous across LUs. In the absence of snow cover, daily average T s was highly variable among LUs due to variations in vegetative cover, with a standard deviation (SD) greater than 5°C, and relatively uniform (SD < 1.5°C) within LUs. Mean annual soil temperature differences among LUs of 5.2°C was greater than those of 4.4°C associated with a 910‐m elevation difference within the RCEW. In this environment, effective T s simulation requires representation of relatively small‐scale (<20 m) LUs due to the deterministic spatial variability of T s .